(untitled) (Research, Society and Development, 2022)
Global demand for natural pigments and dyes has increased much in recent years, driven by a heightened awareness of the toxic effects of various synthetic dyes on pollution of the environment and health human. The pigments and colorants obtained through plants and microbes are the primary source exploited by modern industries. Among the other non-conventional sources, filamentous fungi particularly are known to produce an extraordinary range of colors including several chemical classes of pigments such as melanins, azaphilones, flavins, phenazines, and quinines. The objective of this work was to evaluate the production of pigments produced by Talaromyces spp. and its antimicrobial activity. In this context, strains of the fungi Talaromyces spp. were isolated from soil of biome Caatinga and showed production of dark red, red and yellow pigments. Almost all fungi were able to grow and produce soluble pigments in the solid medium containing different carbon sources (sucrose, fructose, glucose, maltose, and starch), as well as in different salinity concentrations (0.5%, 1%, 2%, 4% and 6%), kept at room temperature (28ºC). All the extracted pigments showed antimicrobial activity against to bacteria Gram negative, as well as to yeasts, evidencing the high potential of application in the textile industry to produce antimicrobial fabrics.